PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN PROMOSI TERHADAP MINAT NASABAH MENABUNG PADA BANK SYARIAH CABANG ULAK KARANG KOTA PADANG - Nazzarudin Aziz; Vito Shiga Hendrastyo (JURNAL PUNDI, 2019)
The survey conducted by Top Brand Indonesia obtained the latest data in 2016 indicates that the interest of saving customers at Bank Syariah Mandiri low is no exception in Bank Syariah Mandiri branch of Ulak Karang. It can certainly be influenced by various things, namely whether the quality of services provided by employees of Bank Syariah Mandiri is still less satisfactory, the promotion made by Bank Syariah Mandiri is still less attractive, and still decreased the level of customer confidence in Bank Syariah Mandiri.From the results that researchers do can be concluded that the quality of service, trust and promotion influence together on the interest of customers in saving. For the quality of service and promotion have a significant and positive impact on the interest of customers in saving but in the trust does not have a significant and negative impact on interest of customers in saving.